SELAYANG PANDANG KETIMPANGAN GENDER DALAM BAHASA INDONESIA - * Jupriono (Universitas 17 Agustus 1945 Surabaya, 2010)
Abstract. Some vocabulary and Indonesian phrases reflect that: a woman keeping a patient's life but a man being the lord of life; women always being the victims and blamed, and no comment toward man; men being common to be in charge of any position, accomplishment, organization, or job; it is, however, considered an optional